A structural model of burnout syndrome, coping behavior and personality traits in professional soldiers of the Slovene armed forces - Serec, Maša (Zdravniški vestnik, 2012)
Background: This study explored how adequately the additive and mediational models could explain the relationships between personality traits and coping behavior in predicting burnout syndrome in professional soldiers of the Slovene Army. The additive model suggests that personality and coping are independent, unique contributors to maladjustment outcomes. The mediational model, on the other hand, suggests that personality factors predispose people to use particular coping strategies that tend to be less effective for adjustment. Methods: A total of 390 soldiers (87% response rate) completed theEysenck Personality Questionnaire, the Ways of Coping Questionnaire and theMaslach Burnout Inventory. Results: The structural equation modeling confirmed an adequate fit only of the additive model. As hypothesized, emotional exhaustion was positively associated with neuroticism and emotionoriented coping. Depersonalization was positively associated with psychoticism, and personal accomplishment was positively associated with extraversion and problem-oriented coping, and inversely with neuroticism and emotion-oriented coping. Conclusions: To reduce burnout in the Slovenian Army,it may be of great benefit to provide training of effective stress-copingmechanisms, and create peer support groups among soldiers. Such intervention should be especially beneficial for soldiers with a vulnerable personality structure (high neuroticism and psychoticism and low extraversion).
Keywords: Burnout, Professional; Izgorevanje poklicno; Military Personnel; Osebnost, ocenitev; Osebnostni testi; Personality Assessment; Personality Tests; Psychology; Stres psihološki; Stress, Psychological; Vojaško osebje